2017
DOI: 10.1182/blood-2016-09-742999
|View full text |Cite
|
Sign up to set email alerts
|

Mice with a deficiency in CLEC-2 are protected against deep vein thrombosis

Abstract: Key Points Absence of CLEC-2 abrogates venous thrombosis. Podoplanin expression is upregulated in the vessel wall and correlates with the degree of thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
171
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(180 citation statements)
references
References 46 publications
4
171
1
4
Order By: Relevance
“…The ideal targets for LEDVT therapies are eliminating the embolic capacity of existing thrombi, reconstructing unobstructed blood flow, maintaining venous valve function, and preventing further thrombosis . However, the molecular mechanism of LEDVT remains unclear, which greatly limits the screening for LEDVT diagnostic markers …”
Section: Introductionmentioning
confidence: 99%
“…The ideal targets for LEDVT therapies are eliminating the embolic capacity of existing thrombi, reconstructing unobstructed blood flow, maintaining venous valve function, and preventing further thrombosis . However, the molecular mechanism of LEDVT remains unclear, which greatly limits the screening for LEDVT diagnostic markers …”
Section: Introductionmentioning
confidence: 99%
“…Podoplanin is a sialomucin‐like glycoprotein and has the ability to induce platelet aggregation via interacting with the C‐type lectin‐like receptor (CLEC)‐2 on platelets . Recent experimental studies using mouse models confirmed the important role of podoplanin in the pathophysiology of VTE . Based on these observations, podoplanin‐induced platelet aggregation might be a major driver of brain tumor‐associated VTE.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms underlying the association between pCLEC‐2 and death or recurrence of vascular diseases are still unclear and more studies, especially animal experiments, are needed to explore them. Recently, another role of thromboinflammation of CLEC‐2 has been reported . As AIS may be in fact a thrombo‐inflammatory disorder, the thromboinflammation role of CLEC‐2 may be crucial in the development and pathogenesis of ischaemic stroke.…”
Section: Discussionmentioning
confidence: 99%